European guidelines on perioperative venous thromboembolism prophylaxis: Mechanical prophylaxis. Issue 2 (February 2018) - Afshari, Arash; Fenger-Eriksen, Christian; Monreal, Manuel; Verhamme, Peter
Abstract : N/A: Institutional protocols need to address the indications for pharmacological and mechanical thromboprophylaxis. The use of graduated compression stockings (GCS) and intermittent pneumatic compression (IPC) strongly differs between institutions. As a consequence, no strong recommendations can be made based on the contemporary high-level evidence. Although different clinical practices can be supported, such approaches should be part of an institutional strategy to reduce the burden of venous thromboembolism (VTE). We recommend against the use of GCS alone without pharmacological thromboprophylaxis for prevention of VTE in patients at intermediate and high risk. For patients at high risk of VTE with contraindications for pharmacological thromboprophylaxis, we recommend the use of mechanical prophylaxis and suggest the use of IPC over GCS. However, for those patients receiving pharmacological thromboprophylaxis who are without a very high risk of VTE prophylaxis, we recommend against the routine use of mechanical thromboprophylaxis either with GCS or IPC. We suggest combined mechanical and pharmacological prophylaxis in selected patients at very high risk of VTE prophylaxis and suggest IPC rather than GCS in these selected patients.